MHC‐disassortative mate choice and inbreeding avoidance in a solitary primate. Issue 15 (25th July 2013) - Huchard, Elise; Baniel, Alice; Schliehe‐Diecks, Susanne; Kappeler, Peter M.
Abstract: Sexual selection theory suggests that choice for partners carrying dissimilar genes at the major histocompatibility complex (MHC) may play a role in maintaining genetic variation in animal populations by limiting inbreeding or improving the immunity of future offspring. However, it is often difficult to establish whether the observed MHC dissimilarity among mates drives mate choice or represents a by‐product of inbreeding avoidance based on MHC‐independent cues. Here, we used 454‐sequencing and a 10‐year study of wild grey mouse lemurs ( Microcebus murinus ), small, solitary primates from western Madagascar, to compare the relative importance on the mate choice of two MHC class II genes, DRB and DQB, that are equally variable but display contrasting patterns of selection at the molecular level, with DRB under stronger diversifying selection. We further assessed the effect of the genetic relatedness and of the spatial distance among candidate mates on the detection of MHC‐dependent mate choice. Our results reveal inbreeding avoidance, along with disassortative mate choice at DRB, but not at DQB. DRB‐disassortative mate choice remains detectable after excluding all related dyads (characterized by a relatedness coefficient r > 0), but varies slightly with the spatial distance among candidate mates. These findings suggest that the observed deviations from random mate choice at MHC are driven by functionally important MHC genes (like DRB) rather than passively resulting from inbreeding avoidance and further emphasize the need for taking into account the spatial and genetic structure of the population in correlative tests of MHC‐dependent mate choice.